PP.31.08: PREVALENCE AND CHARACTERISTICS OF NOCTURNAL HYPERTENSION IN PREHYPERTENSIVE SUBJECTS. (June 2015) - Camafort-Babkowski, M.; Sobrino-Martinez, J.; Domenech, M.; Vinyoles-Bargallo, E.; Ruiz, J. Saban; Moncho, J. Montagud; Delgado, J. Maraver; Medrano, A. Segarra; Gómez, L. Cuadrado; Garcia, J. Mediavilla; Garcia, J. Rodriguez; Chillón, F. Gamazo; et al.
Abstract : Objective: To analyze the prevalence of nocturnal hypertension (NHT) and their associated predictive factors in non-hypertensive subjects with high normal BP values. Design and method: 453 subjects with office BP values between 130–139mmHg of systolic BP (SBP) and / or 85–89 mmHg for diastolic BP (DBP) underwent 24-h ambulatory BP monitoring (ABPM), medical history, physical examination, EKG and laboratory investigations. Nocturnal Hypertension (NHT) was defined as BP higher or equal to 120 mmHg for SBP and / or higher or equal to 70 mmHg for DBP during night-time. Results: Mean age was 49.79 years ± 10.28 years, with a 51% of women. The prevalence of NHT was 58.1%; It was more frequent in males (68.9% vs 47.6% in men than women, p < 0.001) with a greater prevalence of masked hypertension (84.6% vs 39.2%; p < 0.001), higher office BP (SBP 134.67 ± 4.17 vs 133.49 ± 4.9 mmHg; p = 0.007 and DBP 84.75 vs 83.76 ± 3.8 ± 4.7 mmHg; p = 0.015) and a greater waist circumference (92.1 ± 10 vs 89.6 ± 13 cm; p = 0.026). As for the laboratory and EKG investigations higher values of plasma creatinine (0.82 ± 0.17 vs 0.76 ± 0.1 mg / dl; p < 0.001) and increased left ventricular enlargement determined by the R voltage in aVL (0.48 ± 0.2 vs 0 41 ± 0.2 mV; p = 0.004) were found. Conclusions: Nocturnal hypertension affects more than a half of prehypertensive subjects, mainly males with high waist circumference. A ABPM would be reasonable for the diagnosis and management of this situation since this subpopulation has more target organ damage as worse renal function and increased left ventricular enlargement.